Dalam Kaitannya Akuntansi Rumah Tangga, Menyoroti Keluarga Muslim - Areena Kaswarhiena; Riska Rahmayanti; Nurazizah Nurazizah (Rumah Jurnal STAIN Majene, 2023)
Accounting practices are appealing to be studied in a family which is the smallest unit in society. The economic activities of the family have unwittingly demonstrated accounting practices. The purpose of this study is to reveal these practices and assist in the preparation of financial reporting as in the concept of accounting This research is qualitative with a case study approach. the location of the research was in Parepare, South Sulawesi. The Informants were Muslim families who had children where both parents worked. The data collected was then analyzed through data reduction, data presentation, and drawing conclusions. The result of the research discloses that receipts and expenditures of the familiy can be prepared according to accounting cycle starting from transaction recording, classification until preparation of financial statements. The types of transactions obtained from Islamic family during preparing the financial statements are cash, account receivable, equity, revenue, family expenditure, zakat, Infaq, Shadaqah expenditure as well as capital expenditure.